MANAGEMENT OF ADULT EDUCATION DEVELOPMENT IN A TERRITORIAL COMMUNITY - Кравченко, Олена (SWorldJournal, 2026)
The article explores the peculiarities of managing adult education development at the level of territorial communities amidst contemporary globalization transformations, decentralization, and the post-war recovery of Ukraine. The relevance of the topic i